Ter ou ser? materialismo e simplicidade voluntária no consumo de moda em brechós - Santos, Talita de Castro (2019)
The present research had the objective of presenting the results of the research carried out in a brechó located in the city of João Pessoa - PB, in the period between February and March 2019 with the purpose of investigating the relationship of the respondents with motivating factors for fashion consumption in thrift stores , based on voluntary simplicity and materialism. The collection instrument used is composed of 51 questions, where 6 are objective questions and 45 are likert scale. In order to obtain the results presented here, statistical analyzes were used with the support of Excel and SPSS software version 22, for tabulation and compilation of the data, respectively. The socioeconomic profile of the interviewees is 71% with an age group between 22 and 41 years of age; 47% with post-graduation; 36% employed in private companies and 32% with income bracket between 1000 and 3000 reia. Regarding the interviewees' purchase relationship with the brechó, 53% said they bought and sold pieces for the brechó and when asked about how to dispose of pieces that they no longer use, 49% reported donating the pieces to friends / relatives, 27% donate to charity and only 18% sell to thrift stores. Cronbach's alpha measured was 77% considered satisfactory, that is, the data are in agreement with the research objectives. Statistical tests were used to verify the correlation strength between pairs of variables and if there were significant differences between the variables, in order to use them in isolated studies with the support of more robust statistical analyzes.